RECLAIMING OF HISTORICAL PIAZZA IN ISLAMIC CAIRO AL-HUSSEIN PIAZZA CASE STUDY - Ahmed, Hassan (Journal of Islamic Architecture, 2019)
Urban public space and social interaction play an important role in the urban environment and can be a refuge from the hustle and bustle of city life. Public space refers to non-domestic physical sites that are distinguished by their relative accessibility such as parks, restaurants, cafes, the street. Al Hussein piazza is one of the oldest and largest areas in Fatimid Cairo. Many of the activities organized throughout the year periodically. In recent years, some infringements occurred formal or informal. It led to poor urban value. This study aims to evaluate the current situation of Al- Hussein piazza and redesign it from an integrated sustainable vision to reclaim it again for visitors. The methodology that was used in this study is a field survey of the piazza and do some interviews. The research shows that multiplicity causes deterioration in the region, which can be classified as physical degradation, environmental degradation, and social deterioration.